Competition, non-financial measures and the effectiveness of management control system - Ibrahim, Mohd Yussoff; Ibrahim, Daing Nasir; Sanda, Ahmaru Umaru (Universiti Utara Malaysia, 2001)
This paper reports the results of an empirical study examining the relationship between the emphasis on non-financial measures and two other variables; the intensity of competition and the effectiveness of a management control system, in a manufacturing company. Two important issues focused in the study are: does competition compel managers to utilize more non-financial measures in decision making and is the emphasis given to non-financial measures worthwhile? Data from 105 manufacturing companies throughout Malaysia were analyzed using correlation and regression analysis. The results of both analyses indicate that the emphasis given to non-financial measures in decision making has a positive correlation with the effectiveness of a management control system and secondly, the intensity of competition faced by an organization is positively correlated with the emphasis on non-financial indicators. Descriptive analysis was also performed to evaluate the distribution of emphasis on non-financial measures by the age, location, ownership, size of an organization and its industry.